Áreas de atuação de pesquisadores como input para caracterizar a atuação institucional - Galdino, Rosangela (2019)
Bibliometric studies are used in the evaluation of scientific activity, using as a source of information databases such as the Web of Science, Scopus and Lattes Platform. Aiming to contribute to the characterization of the performance of science, technology and innovation institutions (ICTs), through bibliometric studies, the general objective of this research was to characterize the performance profile of an ICT, using information about the areas of expertise of its teachers. -searchers present at the Lattes Platform. The method used was the case study and the case unit of the Instituto Federal de Educação, Ciência e Tecnologia de São Paulo (IFSP). Bibliometrics was used as an information analysis technique and the Lattes Platform was used as a source of information. The sample analyzed comprised 2485 curricula of 2527 active researchers from 2010 to 2018. The results comprised a set of indicators on the case unit's performance profile, graphically represented in the form of mandalas and network graphs: 1) institution; 2) proximity of actuation between the campuses of the case unit. It can be concluded that the results achieved can contribute to bibliometric studies at the institutional level, by systematizing through the analysis of the researchers' areas of activity the identification and visualization of the performance profile of an ICT, as well as the identification of areas whose interest for collaboration between teachers is potentially greater.